Development of A Mobile-Based Application for Ordering House Interior and Exterior Designs - Saputro, Prasetyono Hadi; Fachrie, Muhammad (International Journal Software Engineering and Computer Science (IJSECS), 2023)
This study focuses on a design services company lacking a computerized information system for managing customer orders and financial calculations. The absence of a structured reporting system for daily, weekly, monthly, and annual periods hinder efficient operations. We employ a descriptive research method with an object-oriented and prototype development approach. The programming language used is Kodular, and Firebase is utilized for database storage. The research results in the creation of a mobile-based interior and exterior design information system. It aids in order management, allows customers to check order statuses, minimizes calculation errors, and facilitates report generation. This system significantly streamlines company operations and enhances productivity.